The European Charter for Regional or Minority Languages by Ukraine - Csernicsko Istvan; Черничко Степан; Csernicskó István (Valerij Padjak-II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2013)
Ukrajna első alkalommal 1999-ben ratifikálta a Regionális vagy Kisebbségi Nyelvek Európai Chartáját, ám az Alkotmánybíróság hatályon kívül helyezte a törvényt. 2003-ban ismét megtörtént ratifikálás, ám a Charta azóta is politikai és társadalmi viták kereszttüzében áll, alkalmazása esetleges. Polemizálnak a Charta hatálya alá eső nyelvek, a nemzetközi dokumentum célja, alapfogalmai és terminológiája kapcsán egyaránt. A tanulmány a Charta ukrajnai alkalmazásának sajátos vonásait mutatja be.

Резюме. Україна в 1999 році ратифікувала Європейську хартію регіональних мов або мов меншин, але Конституційний суд України скасував закон про її ратифікацію. У 2003 році Верховна Рада знову ратифікувала Хартію. З того часу Хартія є підставою для суспільних і політичних дискусій. У статті відображена проблематика ратифікації міжнародного документу, суть та особливості застосування Хартії в Україні.

Abstract. Ukraine had ratified the Charter in 1999, but the Constitutional Court impeded its coming into force. In 2003 Ukraine ratified the Charter again; however, this version of the Charter specifies more restricted rights then the previous one. The implementation of the Charter is still a matter of debate in the country. The list of languages protected by the Charter also raises a few questions. According to the national powers the aim of the Charter is to protect languages near extinction, therefore it could not be extended to the Russian, German, Romanian, Hungarian or Slovak languages. But the Ukrainian language should get the protection, which is in danger in the eastern and southern parts of the country.
Європейська хартія регіональних мов або мов меншин в Україні
https://www.kmf.uz.ua/hun114/letoltes/acta/ActaAcBereg2013_2.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/157029
Keywords: minority languages; regional languages; Ukraine; European Charter